Course Degree in Rural Education - Area Agricultural Sciences in the IFSULDEMINAS/Campus Inconfidentes - João Batista Begnami; Aloísia Rodrigues Hirata; Luiz Carlos Dias da Rocha (Universidade Federal do Norte do Tocantins, 2018)
The present article aims to present a first effort to systematize and analyze the experience of collective and interinstitutional construction and the beginning of the implementation of the Licentiate Course in Rural Education - Agricultural Sciences area (LECCA), organized in alternation and agroecological approach, at the Federal Institute of Education, Science and Technology of the South of Minas Gerais (IFSULDEMINAS). The Pedagogical Course Project, as well as the documents generated for the construction of this and for the implementation of the course and the observations about the initial pedagogical practices were the main sources of data collection for the elaboration and analysis of this work. The present systematization constitutes an important strategy of visibility and reflection on the peasant reality and the politico-pedagogical practices of LECCA. This experience inspired by the paradigms of Rural Education and Pedagogy of Alternation evidences an ambivalent field of challenges and tensions in academic institutions, but it also brings to reflection the potential of the public institution of higher education as a place of innovation and experimentation of the new paradigms of construction of the scientific knowledge, committed to a new project of school, rural and society.